Water-energy-food planning and operations framework for river basins with a case study on the Blue Nile - Basheer, Mohammed; Siddig, Khalid; Ringler, Claudia (Elsevier, 2024)
Infrastructure in river basins is essential to achieving several Sustainable Development Goals (SDGs), including SDG 2 on zero hunger, SDG 6 on water and sanitation, and SDG 7 on affordable and clean energy. However, important tradeoffs and synergies need to be navigated across these goals as both water and resources for infrastructure investments are limited. In transboundary river basins, such tradeoffs can transcend countries, creating a complex, interconnected system of water-energy-food linkages. With increasing pressures on the Blue Nile’s water resources from population and economic growth and climate change, an analytical framework for joint planning of these essential human development goals at a fine temporal resolution and considering multi-national priorities can enhance the potential to achieve water, energy, and food security. In this study, we develop and apply a framework for water resources planning in the Blue Nile using four steps: (1) understanding the water-energy-food nexus management landscape through stakeholder engagement and literature review; (2) developing a detailed daily simulator that captures major nexus components and objectives at a fine temporal scale; (3) linking the simulator to an Artificial intelligence-based search algorithm to design efficient agricultural and dam operation portfolios considering national and sectoral priorities; and (4) presenting the results using interactive visualization tools to facilitate dialogue and support decisions. Our results identify efficient operation plans for large dams on the Blue Nile for alternative cropping patterns in expanded irrigation areas in Sudan that minimize tradeoffs across water, energy, and food objectives.